TEACHING OF GAMES AND PLAYING IN PHYSICAL EDUCATION IN HIGH SCHOOL: EDUCATIONAL EXPERIENCES IN AN INTERCULTURAL AND ANTI-RACIST PERSPECTIVE - Maldonado, Daniel Teixeira (2021)
The objective of this work was to report and analyse a political-pedagogical experience with the teaching of games and playing of different cultures during Physical Education in High School. The experience was lived with a 2nd year class of the Mechanics course integrated with the High School of the Federal Institute of São Paulo for six months. The teacher's records and the work done by the students in the classes were data sources for the writing of this article. Board games and playing from various parts of Brazil and the world were experienced. The social markers of class, race, gender, religion, and generation that cross these bodily practices have been problematized. At the end of the educational project, we highlight our effort to build educational practices that value differences and multiculturalism, developing an intercultural and anti-racist pedagogy in Physical Education classes.